2023
DOI: 10.3390/ijms24065874
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Anti-Müllerian Hormone in Regulating Seasonal Reproduction in Animals: The Example of Males

Abstract: Seasonal reproduction is a survival strategy by which animals adapt to environmental changes to improve their fitness. Males are often characterized by a significantly reduced testicular volume, indicating that they are in an immature state. Although many hormones, including gonadotropins, have played a role in testicular development and spermatogenesis, research on other hormones is insufficient. The anti-Müllerian hormone (AMH), which is a hormone responsible for inducing the regression of Müllerian ducts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
0
0
Order By: Relevance
“…The increase in testicular AMH expression can cause an elevation of apoptosis and a reduction in cell proliferation [30]. Regarding the seasonal breeders, a high expression level of AMH genes during the non-breeding season and a low expression level during the breeding season has been shown in male animals [34]. Similarly, a study on the quail testis demonstrated an upregulation of AMH when the testis was seasonally regressed [35].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in testicular AMH expression can cause an elevation of apoptosis and a reduction in cell proliferation [30]. Regarding the seasonal breeders, a high expression level of AMH genes during the non-breeding season and a low expression level during the breeding season has been shown in male animals [34]. Similarly, a study on the quail testis demonstrated an upregulation of AMH when the testis was seasonally regressed [35].…”
Section: Discussionmentioning
confidence: 99%